Physiologically based pharmacokinetic modeling : (Wiley-Interscience, 2005)
This book presents an overview of the underlying principles of PBPK model development. Then it provides a compendium of PBPK modeling information, including historical development, specific modeling challenges, and current practices. In addition to pinpointing specific information, readers can explore diverse modeling techniques and applications. An authoritative reference for toxicologists, ecotoxicologists, risk assessors, regulators, pharmacologists, pharmacists, and graduate students in pharmacokinetics and toxicology, Physiologically-Based Pharmacokinetic Modeling compiles information from leaders in the field and discusses future directions for PBPK modeling.